2021
DOI: 10.3390/cancers13092161
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Citrate Levels and Specific Transcriptional Signatures Associated with Quiescence of CD34+ Progenitors Predict Azacitidine Therapy Failure in MDS/AML Patients

Abstract: To better understand the molecular basis of resistance to azacitidine (AZA) therapy in myelodysplastic syndromes (MDS) and acute myeloid leukemia with myelodysplasia-related changes (AML-MRC), we performed RNA sequencing on pre-treatment CD34+ hematopoietic stem/progenitor cells (HSPCs) isolated from 25 MDS/AML-MRC patients of the discovery cohort (10 AZA responders (RD), six stable disease, nine progressive disease (PD) during AZA therapy) and from eight controls. Eleven MDS/AML-MRC samples were also availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 92 publications
(149 reference statements)
4
7
0
Order By: Relevance
“…In the process of epigenetic modulation, DNMT1 (a maintenance DNA methyltransferase) was defined as one of the core PCGs related to the AZA response. Previously, it was demonstrated that DNMT1 serves as a pharmacologic target of HMAs (65), and down-regulation of DNMT1 expression in AZA nRESPs has been attributed to noncycling status and reduced replication of HSPCs in these patients (18). Another core PCG of epigenetic mechanisms involved in the response to AZA was the EZH2 gene, which was also specifically down-regulated in our cohort of AZA nRESPs.…”
Section: Cancer Genomics and Proteomicssupporting
confidence: 50%
See 4 more Smart Citations
“…In the process of epigenetic modulation, DNMT1 (a maintenance DNA methyltransferase) was defined as one of the core PCGs related to the AZA response. Previously, it was demonstrated that DNMT1 serves as a pharmacologic target of HMAs (65), and down-regulation of DNMT1 expression in AZA nRESPs has been attributed to noncycling status and reduced replication of HSPCs in these patients (18). Another core PCG of epigenetic mechanisms involved in the response to AZA was the EZH2 gene, which was also specifically down-regulated in our cohort of AZA nRESPs.…”
Section: Cancer Genomics and Proteomicssupporting
confidence: 50%
“…Current research activities are usually focused on the identification of an ideal, single biomarker whose alterations (such as a mutational change or transcription deregulation) would be predictive of treatment response with high sensitivity and specificity. The patient capability to respond to AZA and the identification of prediction markers have been repeatedly addressed (11,12,18). However, given the genomic heterogeneity of the disease, no universal biomarker has been identified thus far.…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 99%
See 3 more Smart Citations